Pelatihan Unit Praktikum (Fisika) Mata Kuliah IPA Sekolah II bagi Asisten Praktikum Laboratorium IPA - Syarful Annam; Nurhayani H. Muhiddin; Shoffan Fatkhulloh; Nur Rahmah Sangkala; Hasanuddin Hasanuddin (Postgraduate Program, University of Mataram, 2026)
Practicum activities play an important role in science learning as they enhance students’ conceptual understanding and science process skills. However, the implementation of practicums is often not optimal due to the limited competence of practicum assistants, both in technical and pedagogical aspects. Therefore, this community service activity aims to improve the competence of practicum assistants through physics practicum unit training in the IPA Sekolah II course. The method used is practice-based training consisting of preparation, implementation, mentoring, evaluation, and reflection stages. Data collection techniques include pre-test and post-test questionnaires, observation, and documentation, while data analysis is conducted using descriptive quantitative and qualitative approaches. The results show an improvement in participants’ competencies across all measured aspects, including equipment operation, pedagogical and practicum management skills, troubleshooting, as well as attitudes and readiness. The average score increased from 3.03 in the pre-test to 3.45 in the post-test. This indicates that the training was effective in improving the overall competence of practicum assistants. Thus, this activity contributes to supporting more effective and high-quality practicum implementation.